Optimalisasi Pelayanan Administrasi Balik Nama Sertifikat Tanah Guna Efisiensi Tata Kelola Pertanahan yang Berkepastian Hukum (Studi Kasus di Desa Ngombakan, Kecamatan Polokarto, Kabupaten Sukoharjo) - Salsabila Anggraini Zakaria; Sri Sumartiningsih; Sumidi S (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examined is the effectiveness of administrative services in the land certificate transfer process in Ngombakan Village, Polokarto District, Sukoharjo Regency. The study was conducted using a normative juridical approach supported by empirical data. Analysis of legal provisions indicates that the transfer mechanism is regulated by Law Number 5 of 1960 concerning Agrarian Principles and Government Regulation Number 24 of 1997 concerning Land Registration, which emphasize the principle of legal certainty through land rights registration. The findings indicate the need to optimize administrative services in Ngombakan Village by strengthening the role of the village government as a facilitator, providing simple digital guides, and improving community legal literacy.